Students' Perspectives on the Use of Tiktok as a Medium to Increase Motivation and English Speaking Skills - Syafryadin (Scopus ID 57212212579, WoS ID: ABI-8120-2020), Syafryadin; Ramadhan, Dio Putra; Sanjaya, Hengki Kris; Sari, Dwi Indah; Melfia, Leza (PROJECT (Professional Journal of English Education), 2026)
This study explores students' perspectives on using TikTok as a medium to improve motivation and English-speaking skills in the context of informal learning. Drawing on Krashen's Second Language Acquisition Theory, Media Wealth Theory, and Keller's ARCS Motivation Model, this study examines how educational content from influencers contributes to the learning process in the digital age. This study uses a descriptive qualitative approach through in-depth interviews with students who actively use TikTok to learn English. Data was analyzed using an interactive model that included data reduction, data presentation, and a conclusion drawn. The findings show that students independently choose educational content that increases their learning autonomy and intrinsic motivation. TikTok's multimodal and short-form characteristics have proven effective in improving vocabulary mastery, pronunciation accuracy, and speaking confidence through daily conversation simulations. Additionally, a relaxed digital environment helps lower psychological barriers, such as anxiety when speaking. However, there are challenges, including a lack of real, practical opportunities in a formal classroom environment. Overall, students rate TikTok as a very promising add-on tool for supporting English-speaking proficiency outside the traditional classroom.